The Correlation of Leadership and Leader-Member Exchange on the Performance of SMEs by Mediation of Organizational Commitment - Elyzabeth Wijaya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
This study aims to analyze the relationship between the variable leadership and organizational commitment, to analyze the relationship between the variable leader-member exchange and organizational commitment, to analyze the relationship between the variable leadership and performance, to analyze the relationship between the variable leader-member exchange and performance, and to analyze the relationship between organizational commitment and performance. This research method is a quantitative approach. The respondents of this study were 403 SMEs owners in Banten Indonesia. The data collection technique used by researchers is sampling with simple random sampling. The scale used in the study to fill in each question item uses a Likert scale with 5 (five) alternative answers, namely strongly agree, agree, undecided, disagree, strongly disagree. Data were obtained by distributing online questionnaires via social media. Analysis of research data using Structural Equation Model Partial Least Square (SEM-PLS) using SmartPLS software. In this study, the data analysis used was a validity test, a reliability test and a hypothesis test using SEM-PLS on 4 (four) variables. The results of this study are that leadership has a positive and significant effect on organizational commitment, leader-member exchange has a positive and significant effect on organizational commitment, leadership has a positive and significant effect on performance, leader-member exchange has a positive and significant effect on performance, organizational commitment not  significant effect on the performance of SMEs. Leadership has no significant effect on performance through organizational commitment, organizational commitment does not mediate the relationship between leadership and performance. Leader-member exchange has no significant effect on performance through organizational commitment, organizational commitment does not mediate the relationship between Leader-member exchange on performance.